The Internalization of Gapura Pancawaluya Character Education to Realize Insan Kamil at SMAN 5 Bandung - Iwan Sanusi; Dedih Surana; Muhammad Noor Fajri; Arif Basyirurrohman; Suhono (Attractive : Innovative Education Journal, 2026)
The background of this research is driven by the importance of improving the quality of Islamic Religious Education (PAI) learning in secondary schools, especially in overcoming the challenges of teaching that is often rigid and less interesting. This study aims to determine the effect of training on the Market Place Activity learning model on improving the teaching skills of Islamic Religious Education (PAI) teachers in senior high schools in Bandung City. This study uses a quantitative approach with a quasi-experimental method with a one-group pretest-posttest design. The research subjects were 20 PAI teachers from public and private high schools who participated in the training. The instrument used was a teaching skills test before and after the training. The results of descriptive statistical analysis showed an increase in the average score from 72.0 to 80.0. The paired t-test produced a t-count of 3.76 with a p-value of 0.0013 (<0.05), indicating that the training had a significant effect. These results emphasize the importance of training on participatory and applicable learning models in improving the teaching quality of Islamic Religious Education (PAI) teachers.